A Dynamic financial optimization approach to structuring mortgage backed securities in Kenya - Ng'eno, William Kipyegon (Strathmore University, 2018)
Ideally, there should be a match between the demand for housing in an economy and its supply. This would ensure stability in house prices as well as affordability (Munene, 2010). In sub-Saharan Africa, slum populations grow at 4.5 percent per annum (Marx, Stoker, & Suri, 2013). At this rate, slum populations would double every fifteen years. It is expected that Nairobi 's population will grow to over 8 million by the year 2025 given the rapid urban population growth rate. Unlike cities in developed countries, this increase is not accompanied by a corresponding improvement in socio-economic and environmental development (Mutisya & Y arime, 2011 ).
A Research project submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Science in Actuarial Science at Strathmore University
Keywords: mortgage securities; Financial optimization; Loans